Banking in the metaverse: a new frontier for financial institutions - Yogesh Dwivedi (International Journal of Bank Marketing, 2023)
Purpose: Technological advancements have catalyzed disruption in the banking sector. The impact of the metaverse on the banking sector is no exception. In view of this, the current paper aims to provide valuable insights into four key areas (i.e. corporate banking, retail banking, banking employees and public policy) that the metaverse could significantly disrupt. Design/methodology/approach: Insights into four key areas of the banking sector that the metaverse could significantly impact were gathered from various invited contributors. Findings: The invited contributors first introduce the association between their respective key areas with the metaverse. Subsequently, the opportunities and challenges relevant to the key areas were identified. Finally, future research agendas were proposed for the attention of all relevant stakeholders. Originality/value: The metaverse's impact on key areas of the banking sector is discussed in this paper. Following the metaverse's potentially wide application in the banking sector, insights from the invited contributions offer great value to the relevant stakeholders.